Do Vazio Construtivo ao Espaço-Entre. Corpo, Limite, Luz e Espaço. - Manuel Rui Cunha Domingos (2016)
This research2 - From being a constructive emptiness to that of an in-between space. Body, Limit, Light and Space - aims at studying space from the perspective of three the main "protagonists" (critical features) that take part in the process of idealisation, imagination and configuration of space. The body - is the measure, it is the reference and implies a sensitive experience of space; the limit - frames its experience; and light - shapes and reveals space. In this way it is possible to confront the construction of space with the emptiness that shapes it - the invisible of the construction. Or, in other words, with the constructive emptiness that configures the function of space as an in-between space. The thesis is structured in two parts: the first one, mainly theoretical, reflects upon those three "protagonists" seeking to show their role (body, limit and light) in the process of conception of space. Each key feature will be analyzed in detail in a separate chapter - "Space-Body", "SpaceLimit", "Space-Light" - with the aim of reflecting about its meaning and understanding and how they act and participate in the creative process of thinking and constructing architectural space. The second part, mainly empirical, focuses on the discussion of three existing case studies with the aim to analyse the implications and potential problems of applying these three 'protagonist' to real space. Three twentieth-century buildings designed by three architects were selected as exemplary of embodying in-between space(s) and their "protagonists". They are the Casa-Estúdio Luis Barragán - in this case we reflect on how the in-between space confronts the body and produces ("in it" and "with it") an emotional architecture; the Yale Center for British Art (Louis I. Kahn) - here we reflect upon the inhabitable limits of the in-between space; and the Santa Maria Church (Álvaro Siza) - where we deal with the role of light in framing and shaping space. The argument of the thesis focuses on the creative process that develops design "from being a constructive emptiness to that of an in-between space". This process allows, on the one hand, to reflect on the relationship between "space and its protagonists" and, on the other hand, to question how in preliminary stages of each design and project-oriented thinking process, it is possible to build a critical narrative directly involved with the imagination of the "emptiness".